Scientific Publications’ Bibliometric Analysis of Application-Level TCP/IP Models’ Communication Protocols for the Internet of Things - Borysov, O. (ХДАК, 2024)
A bibliometric analysis of publications on application-layer communication protocols in the context of the Internet of Things technologies have been conducted. The study highlights signifi cant disparities in scientifi c attention given to various protocols, emphasizing the dominance of MQTT and CoAP in the scientifi c literature. Data from the Scopus bibliometric database were used to evaluate the level of research activity and the scientifi c community’s interest in MQTT, MQTT-SN, CoAP, STOMP, XMPP, WAMP, AMQP, DDS, OPC UA, and LwM2M protocols. The fi ndings reveal which protocols are at the forefront of contemporary research and hold the most signifi cant potential for further development and implementation in IoT systems. Understanding the current state and prospects of communication protocols provides an essential foundation for developers and researchers to select optimal solutions for IoT systems integration. The relevance of the topic. Despite the immense potential of the Internet of Things to optimize processes and create innovative services, there is a need for more detailed analyses of the relevance and prospects of various application-layer communication protocols in this fi eld. This creates a gap in understanding how to integrate these protocols into IoT systems, their challenges and opportunities, and which strategies may eff ectively address them. A systematic approach and in-depth analysis of these protocols are critical for developers when selecting optimal solutions for their implementation in IoT sys tems. The purpose of the article. To conduct an updated bibliometric analysis of open application-layer communication protocols within the TCP/IP framework, specifi cally MQTT, MQTT-SN, CoAP, STOMP, XMPP, WAMP, AMQP, DDS, OPC UA, and LwM2M are applied. The analysis aims to evaluate the level of research activity and the degree of scientifi c community interest in each protocol using data from the Scopus bibliometric database. The methodology includes data collection and analysis methods from the Scopus database, focusing on publications from the inception of each protocol until 2023. The study fi lters publications by fi elds of knowledge and document types to ensure relevance and signifi cance. Conclusions. The study revealed a considerable dominance of MQTT and CoAP protocols in the domain of the Internet of Things. With its message delivery control levels, client-broker architecture, network quality and speed resilience, detailed documentation, and low resource requirements, MQTT demonstrates considerable advantages over other protocols in most use cases. The CoAP protocol is more suitable for scenarios with such potential data loss as streaming multimedia. Other protocols exhibit primarily specifi c applications and demonstrate low interest from the scientifi c community. These fi ndings coordinate with the study’s purpose and provide a foundation for further research and informed protocol selection in IoT system development.

Здійснено бібліометричний аналіз публікацій щодо комунікаційних протоколів прикладного рівня в контексті технологій Інтернету речей. Дослідження висвітлює значну нерівність у науковій увазі до різних протоколів, підкреслюючи домінування MQTT та CoAP у науковій літературі. Для оцінки рівня дослідницької активності та зацікавленості наукової спільноти щодо протоколів MQTT, MQTT-SN, CoAP, STOMP, XMPP, WAMP, AMQP, DDS, OPC UA та LwM2M було використано дані наукометричної бази Scopus. Результати дозволяють виявити, які протоколи перебувають у центрі уваги сучасних досліджень та мають найбільший потенціал для подальшого розвитку і впровадження в системах IoT. Розуміння поточного стану та перспектив цих комунікаційних протоколів надає важливу основу для розробників та дослідників у виборі оптимальних рішень для інтеграції в IoT-системи
Keywords: інтернет речей; internet of things; bibliometric analysis